Hinokitiol inhibits Aspergillus fumigatus by interfering with the cell membrane and cell wall - Meng, Fanyue; Liu, Xing; Li, Cui; Peng, Xudong; Wang, Qian; Xu, Qiang; Sui, Jialin; Zhao, Guiqiu; Lin, Jing (Frontiers in Microbiology, 2023)
Hinokitiol (β-thujaplicin) is an important component of the essential oil extracted from Chamaecyparis obtuse, which prevents the decay and decomposition of temple and shrine buildings in Japan. Hinokiol has been shown to have a detrimental effect on various fungi such as Candida albicans and saprophytic fungi. However how hinokitiol works against Aspergillus fumigatus (A. fumigatus) has not been claimed. This study aims to investigate the adverse effects of hinokitiol on the disruption of the cell wall and cell membrane of A. fumigatus and to explore possible potential mechanisms or pathways. According to our results, hinokitiol negatively altered mycelium morphology, growth density, and cell plasma composition content. When incubated with human corneal epithelial cells (HCECs), hinokitiol saw a safe effect with concentrations below 12 μg/mL. Hinokitiol was shown to increase the cell membrane's permeability by decreasing the cell membrane's ergosterol content. The integrity of the cell wall was disrupted, as well as a significant increase in chitin degradation and chitinase activity. As determined by RNA-seq results, subsequent analysis, and qRT-PCR, altered transcript levels of cell walls and cell membranes-related genes (such as eglC) illustrated how hinokitiol affected the genetic profile of A. fumigatus. With this study, we recommend hinokitiol as an effective anti-A. fumigatus agent by reducing the amounts of key components in the cell wall and membrane by preventing production and accelerating breakdown.